2005
DOI: 10.1007/s00244-005-8011-8
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Pesticides, Polychlorinated Biphenyls (PCBs), and Heavy Metals in Sediments From the Dniester River, Moldova

Abstract: The aim of this study was to evaluate sediments of the Dniester River, in the former Soviet republic of Moldova, for the occurrence of agricultural pesticides, polychlorinated biphenyls (PCBs), and heavy metals. In October 2001, sediment samples were collected at three locations of the Dniester River: upstream, downstream, and at the tributary of the River Byk. DDT and its metabolites were observed most frequently. Total DDT sediment concentrations ranged from 8.2 to 34.7 ng/g dry weight with the highest avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 11 publications
2
7
0
Order By: Relevance
“…Similar results were reported by Sapozhnikova et al (2005) on the basis of the Dniestr River research. The authors demonstrated that downstream sampling sites had significantly higher concentration of total PCBs as compared with the upstream samples.…”
Section: The Input Of Pcbs From Surface and Groundwater Runoffsupporting
confidence: 93%
“…Similar results were reported by Sapozhnikova et al (2005) on the basis of the Dniestr River research. The authors demonstrated that downstream sampling sites had significantly higher concentration of total PCBs as compared with the upstream samples.…”
Section: The Input Of Pcbs From Surface and Groundwater Runoffsupporting
confidence: 93%
“…Less chlorinated PCBs are relatively easily metabolized, are not so highly persistent and are therefore not so readily detected in higher organisms. However, PCBs with low chlorine numbers and their hydroxylated products have been measured in sediments and in aquatic organisms such as mussels and fishes (Sapozhnikova et al, 2005;Sakiyama et al, 2007;Sakiyama, unpublished data). In addition, it has been experimentally shown that PCBs with low chlorine numbers are metabolized to OH-PCBs in the mammalian body (Brandt et al, 1982;Wehler et al, 1989).…”
Section: Discussionmentioning
confidence: 96%
“…77, 126 and 169) having dioxin-like properties were reported to be the most toxic congeners [24]. Among them, the congener 77 existed in all samples, and its concentration was not found to be affected with respect to increasing depth profile from 0 to 30 cm.…”
Section: Toxicitiesmentioning
confidence: 88%